1997
DOI: 10.1139/b97-933
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and ecology of the ascomycete Sarcoleotia globosa in the United States

Abstract: Sarcoleotia globosa (Sommerf.: Fr.) Korf is an ascomycete characterized by stipitate ascomata with a convex apothecium, deep brown to black hymenial surface, greyish brown stipe, and hyaline, clavate, non-to multi-septate ascospores. Collections of S. globosa from Oregon, Washington, and Colorado, United States are reported. Its distribution in North America is extended from previously reported subarctic to arctic regions nearly 2500 km south to the cool temperate zones. Possible association of S. globosa wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It is often found in open vegetation and on disturbed ground (Schumacher and Sivertsen 1987;Jumpponen et al 1997), which fits the sample site of the B. vivipara root system used in this study. It has been suggested to have saprotrophic lifestyle, however, in a survey of stable isotopes, a relatively high enrichment in δ 15 N was shown for species within Geoglossales (Griffith et al 2002).…”
Section: Richness and Community Compositionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is often found in open vegetation and on disturbed ground (Schumacher and Sivertsen 1987;Jumpponen et al 1997), which fits the sample site of the B. vivipara root system used in this study. It has been suggested to have saprotrophic lifestyle, however, in a survey of stable isotopes, a relatively high enrichment in δ 15 N was shown for species within Geoglossales (Griffith et al 2002).…”
Section: Richness and Community Compositionmentioning
confidence: 53%
“…S. globosa within Geoglossales forms small, stipitate fruit bodies, and due to its small size, most likely overlooked in field surveys. Its distribution has previously been described as arctic and sub-arctic, although stretching as far south as cool temperate (Jumpponen et al 1997).…”
Section: Richness and Community Compositionmentioning
confidence: 94%
“…An enclosed hymenium has been observed as well in several other lineages, such as Cyttaria , Erysiphales and Rhytismatales in the Leotiomycetes ( Korf 1983 , Gargas et al 1995 , Johnston 2001 ). Although the name earth tongue implies these fungi are terrestrial and have no direct association found with other organisms, Trichoglossum , Geoglossum and Sarcoleotia globosa have often been recorded in boggy habitats abundant with bryophytes ( Seaver 1951 , Dennis 1968 , Schumacher & Sivertsen 1987 , Spooner 1987 , Jumpponen et al 1997 , Zhuang 1998 ). Ascus apical morphology is one of the major features in distinguishing higher ascomycetes, and operculate ascomycetes as members of Pezizales have an apical or subapical operculum which is thrown back at spore discharge while a definite plug is present in the thickened ‘inoperculate’ ascus apex as in species of the Helotiales ( Korf 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aphothecia did not mature, but Currah et al (1993) suggested P. fortinii as an anamorph of an apothecial member of the Leotiales. Jumpponen et al (1997) pointed out that some members of the Leotiales are very inconspicuous and dark, easily escaping detection. Therefore, sexual reproduction is possible, and could explain the observed diversity, despite the lack of a known teleomorph.…”
Section: mentioning
confidence: 99%